The Use of Recast in Teaching of Grammar for High and Low Achievers (The Case of Spoken Use of English by the Tenth Graders of Nahdhatul Ulama Vocational High School of Ungaran - Candraloka, Olyvia Revalita (LPPM Universitas Mercu Buana Yogyakarta, 2015)
The goals of this study were (1) to find out the effectiveness of recast in teachingof grammar for high achievers, (2) to find out the effectiveness of recast in teaching ofgrammar for low achievers, (3) to find out the effectiveness of clarification request inteaching of grammar for high achievers, (4) to find out the effectiveness of clarificationrequest in teaching of grammar for low achievers, (5) to find out the difference ofgrammar of high and low achievers taught using recast, (6) to find out the difference ofgrammar of high and low achievers taught using clarification request, and the last (7)to explain to what extent the interaction of teaching strategy (recast and clarificationrequest) and the influence of students’ achievements (high and low) to the students’grammar at the tenth grade of SMK NU Ungaran is. This research applies aquantitative method with a factorial design. The experiment class was treated by usingrecast, while the control class was treated by using clarification request. The studiedsubjects were 48 students of grade ten of Nahdhatul Ulama vocational high school ofUngaran which consists of 24 students of an experiment class and 24 students of acontrol class. The results of the research revealed (1) recast is effective to teachgrammar for high achievers,(2 recast is effective to teach grammar for low achievers,(3) clarification request is effective to teach grammar for high achievers,(4) clarificationrequest is not effective to teach grammar for low achievers, (5) there is no significantdifference between high and low achievers on grammar taught by using recast, (6)there is significant difference between high and low achievers on grammar taught byusing clarification request, (7) there is significant interaction of teaching strategy(recast and clarification request) and types of students of achievement (high and low) tothe students’ grammar at the tenth grade of Nahdhatul Ulama vocational high school ofUngaran.Keywords : Achievement, Grammar, Recast